The effectiveness of parenting education based on acceptance and commitment on parenting styles and anxiety in mothers with children with attention deficit / hyperactivity disorder - Khajvand Khoshali, Afsaneh (Applied Family Therapy Journal (AFTJ), 2022)
Aim: Purpose: The purpose of this study was to investigate the effectiveness of parenting education based on acceptance and commitment on parenting styles and anxiety in mothers with children with attention deficit/hyperactivity disorder. Methods: The research design was a quasi-experimental pre-test-post-test type with two experimental and control groups. The statistical population of this research was all mothers with children with attention deficit/hyperactivity disorder. The sample of this study includes 30 mothers with children with attention deficit/hyperactivity disorder who were selected by available sampling method. Then, the mothers of the experimental group received one session of parenting training based on acceptance and commitment based on the protocol of Quinn and Morrell (2009) during nine 90-minute sessions per week, but the control group did not receive any intervention. The research tools were Beck et al.’s anxiety questionnaires (1988) and Bamrind’s parenting style questionnaire (1971). The data was analyzed using the method of analysis of variance with repeated measurements and Spss.23 software. Results: The results showed that parenting education based on acceptance and commitment on authoritarian (F=56.25; P<0.001), authoritarian (F=9.99; P<0.001), permissive parenting styles. (F=3.38; P<0.001) and anxiety (F=5.87; P<0.001) had a significant effect in mothers with children with attention deficit/hyperactivity disorder. Conclusion: It can be concluded that parenting training based on acceptance and commitment is effective on parenting styles and anxiety in mothers with children with attention deficit/hyperactivity disorder and the results of this research can be used to reduce the problems of mothers with children with ADHD. Attention Deficit/Hyperactivity Disorder.